2021
DOI: 10.31234/osf.io/xbyr3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moving beyond "nouns in the lab": Using naturalistic data to understand why infants' first words include uh-oh and hi

Abstract: Why do infants learn some words earlier than others? To explain how and when words are learned, existing theories of word learning prioritize visual information and draw mainly on lab-based studies of noun-to-object mapping. However, words that are more abstract than object nouns, such as uh-oh, hi, more, up, and all-gone, are typically among the first to appear in infants' vocabularies. We combined a behavioral experiment with naturalistic observational research to explore how infants learn and represent this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Routine‐centered language can highlight the communicative consequence of a word rather than its abstract referent (Tamis‐LeMonda et al, 2017). The meaning of the word “uh oh”—one of the words children learn earliest in English—is perhaps that it elicits help, rather than a definable referent (Casey et al, 2021). By focusing on ostensive labeling and how it promotes referent selection, we miss the real‐world dynamics of language input and how it contributes to children's word learning.…”
Section: Consequences Of the Mapping Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine‐centered language can highlight the communicative consequence of a word rather than its abstract referent (Tamis‐LeMonda et al, 2017). The meaning of the word “uh oh”—one of the words children learn earliest in English—is perhaps that it elicits help, rather than a definable referent (Casey et al, 2021). By focusing on ostensive labeling and how it promotes referent selection, we miss the real‐world dynamics of language input and how it contributes to children's word learning.…”
Section: Consequences Of the Mapping Focusmentioning
confidence: 99%
“…Thus, our intuitions about what babies experience and encode in the absence of these biases may not be correct. For example, a recent study found that both parents and researchers believe they can identify the visual referent that a baby will associate with a word like "uh oh" or "bye"; however, these adult intuitions seem to be incorrect (Casey et al, 2021).…”
Section: Thinking From a Baby's Perspectivementioning
confidence: 99%
“…This more comprehensive understanding of motor skill development—grounded in descriptive methods—has generated clinical implications that extend beyond motor skill development (e.g., Adolph et al, 2018). Additionally, recent descriptive work has revealed marked differences between the way that learning is typically tested in the lab and how it occurs in infants' everyday lives (Casey et al, in prep; Kosie & Lew‐Williams, in prep; Clerkin et al, 2017; Fausey et al, 2016). Descriptive studies of infants' everyday environments provide insight into the mechanisms that underlie early learning, help generate informed hypotheses, enable testing of hypotheses in ways that are ecologically valid, allow for comparison of in‐lab and at‐home infant behaviours and contribute to comprehensive theories of infant development.…”
Section: What Do We Mean By “Descriptive Research”?mentioning
confidence: 99%
“…Throughout this paper, we discuss how descriptive research and open science can coexist productively, inspired by existing open‐science practices but geared toward helping those who intend to do open, descriptive research in the field of infant and child development. In an effort to understand and describe the varied dynamics of infants' everyday learning environments, we have increased the use of descriptive methods in our own research over recent years (e.g., Casey et al, in prep; Kosie & Lew‐Williams, in prep). Transparency and replicability are of primary concern, we have drawn inspiration from the practices of other researchers who are doing related descriptive work in a way that is open and transparent (e.g., Bergelson, Amatuni, et al, 2019; Bergelson, Casillas, et al, 2019; Bunce et al, 2020; Casillas et al, 2020; Cychosz et al, 2021; Herzberg et al, 2021; Hoch et al, 2019, 2020; Karasik et al, 2018; Kremin et al, 2020; Mendoza & Fausey, 2021a, 2021b; Romeo et al, 2018; Soderstrom et al, 2021; Sullivan et al, 2020; Warlaumont et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We focus here on the issue of encountering multiple labels for the same referent in early word learning, but children also face the inverse problem-one label for many different referents (e.g., Casey et al, 2021;Meylan et al, 2021). We see these puzzles of word learning as interrelated-and given children's early success in contending with both sources of variability, as evidence that learning happens at multiple levels.…”
Section: Developing Linguistic and Social Knowledge In Tandemmentioning
confidence: 99%